Strategic Oversight and Quality Validation in Spice Production Enhancement: Pengawasan Strategis dan Validasi Kualitas dalam Peningkatan Produksi Rempah-rempah - Miranda, Wiji Amelia; Hudi, Lukman; Anwar, Saiful (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the effectiveness of a comprehensive control management and quality control system in the seasoning production process, focusing specifically on a menu-specific seasoning variant (MSS). The methodology encompassed various stages including material acceptance, sieving, mixing, and final packaging, integrated with stringent control measures such as equipment and facility cleaning, material separation, and machine maintenance. Quality control tests conducted included sodium chloride content, pH analysis, seal strength, and bubble tests. Results indicate that these systematic processes significantly enhance product quality by ensuring compliance with predefined quality standards. The implications of this study suggest that rigorous process oversight and detailed quality assessments can markedly improve the reliability and safety of food seasoning products, providing a framework for industry-wide best practices. Highlights: Process Management: Systematic control measures, including equipment and facility cleaning, ensure a contamination-free production environment. Quality Control: Rigorous testing, including sodium chloride content and pH analysis, guarantees that the products meet established quality and safety standards. Product Compliance: Implementation of advanced control and quality assurance protocols ensures that products consistently comply with industry standards. Keywords: Instant Seasoning, Quality Control, Safety Standards